2016
DOI: 10.1111/his.12990
|View full text |Cite
|
Sign up to set email alerts
|

Small‐cell predominant extranodal NK/T cell lymphoma, nasal type: clinicopathological analysis of a series of cases diagnosed in a Western population

Abstract: Aims Extranodal NK/T cell lymphoma, nasal type (ENKTCL) is usually composed of medium‐ to large‐sized lymphoid cells showing prominent angiotrophism and tumour cell necrosis. We report 13 cases composed predominantly of small lymphocytes diagnosed in the United States and Western Europe. Methods and results Patients included seven females and six males aged 17–75 years. Ten presented with sinonasal and three with buccal disease. Nine had stage IE/IIE and four had stage IV disease. In five of seven patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…Cutaneous ENKTL cases that present erythematous to purpuric patches without a remarkable tumour or nodular lesion show a lower density of tumour cells than other clinical morphologies . These cases are mainly composed of small tumour cells and are less commonly associated with angiocentricity than other clinical morphologies …”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Cutaneous ENKTL cases that present erythematous to purpuric patches without a remarkable tumour or nodular lesion show a lower density of tumour cells than other clinical morphologies . These cases are mainly composed of small tumour cells and are less commonly associated with angiocentricity than other clinical morphologies …”
Section: Discussionmentioning
confidence: 98%
“…Cases of ENKTL consisting mostly of small cells have been described, but the diagnosis of such cases is challenging due to the lack of a visible mass and a subtle histology . Small‐cell‐predominant ENKTL shows a histology characterized by a low proliferation index, lack of angioinvasion and an associated reactive inflammatory background, including small reactive lymphocytes, histiocytes, eosinophils and often many plasma cells . Cutaneous ENKTL cases that present erythematous to purpuric patches without a remarkable tumour or nodular lesion show a lower density of tumour cells than other clinical morphologies .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The angiocentric pattern of ENKTL is usually imperceptible on cytological specimens, while the necrotic background can be more easily observed in Papanicolaou‐stained smears. Cytologically, the neoplastic cells of ENKTL range from small or medium‐sized with irregular nuclei and coarse chromatin to large atypical lymphoid cells with pleomorphic and irregular‐shaped nuclei . A necrotic background consisting of both individual cell necrosis and amorphous necrotic materials has been described a hallmark finding of ENKTL in cytological materials .…”
Section: Discussionmentioning
confidence: 99%
“…Our study demonstrated that CD30+ cutaneous ENKTL presents particular clinicopathological features. ENKTL is predominantly composed of medium‐ to large‐sized lymphoid cells, although cases with predominantly small cells histologically mimicking inflammatory conditions have been reported . CD30 positivity was associated with cellulitis‐like swelling or nodular lesions.…”
Section: Discussionmentioning
confidence: 99%